Two Forms of Electrical Transmission Between Neurons - Faber, Donald S.; Pereda, Alberto E. (Frontiers in Molecular Neuroscience, 2018)
Electrical signaling is a cardinal feature of the nervous system and endows it with the capability of quickly reacting to changes in the environment. Although synaptic communication between nerve cells is perceived to be mainly chemically mediated, electrical synaptic interactions also occur. Two different strategies are responsible for electrical communication between neurons. One is the consequence of low resistance intercellular pathways, called “gap junctions”, for the spread of electrical currents between the interior of two cells. The second occurs in the absence of cells contacts and is a consequence of the extracellular electrical fields generated by the electrical activity of neurons. Here, we contrast the properties of these two different forms of electrical communication and their individual contributions to brain function.